Altered Dependence of Aortic Pulse Wave Velocity on Transmural Pressure in Hypertension Revealing Structural Change in the Aortic Wall. Issue 2 (February 2015) - Gaddum, Nicholas R.; Keehn, Louise; Guilcher, Antoine; Gomez, Alberto; Brett, Sally; Beerbaum, Philipp; Schaeffter, Tobias; Chowienczyk, Philip
<x xml:space="preserve">Abstract</x> Aortic pulse wave velocity (aPWV), a major prognostic indicator of cardiovascular events, may be augmented in hypertension as a result of the aorta being stretched by a higher distending blood pressure or by a structural change. We used a novel technique to modulate intrathoracic pressure and thus aortic transmural pressure (TMP) to examine the variation of intrathoracic aPWV with TMP in hypertensive (n=20; mean±SD age, 52.1±15.3 years; blood pressure, 159.6±21.2/92.0±15.9 mm Hg) and normotensive (n=20; age, 55.5±11.1 years; blood pressure, 124.5±11.9/72.6±9.1 mm Hg) subjects. aPWV was measured using dual Doppler probes to insonate the right brachiocephalic artery and aorta at the level of the diaphragm. Resting aPWV was greater in hypertensive compared with normotensive subjects (897±50 cm/s versus 784±43 cm/s; P<0.05). aPWV was equal in hypertensive and normotensive subjects when measured at a TMP of 96 mm Hg. However, dependence of aPWV on TMP in normotensive subjects was greater than that in hypertensive subjects (9.6±1.6 versus 3.8±0.7 cm/s per mm Hg increase in TMP, respectively, means±SEM; P<0.01). This experimental behavior was best explained by a theoretical model incorporating strain-induced recruitment of stiffer fibers in normotensive subjects and fully recruited stiffer fibers in hypertensive subjects. These results explain previous contradictory findings with respect to isobaric aPWV in hypertensive compared with normotensive subjects. They suggest that hypertension is associated with a profound change in aortic wall mechanical properties possibly because of destruction of elastin leading to less strain-induced stiffening and predisposition to aortic dissection.